Are rugby league players involved in more tackles than normal, prior to an injury sustained during a tackle event?. Issue 22 (17th November 2022) - Hopkinson, Mike; Nicholson, Gareth; Rennie, Gordon; Sawczuk, Thomas; Owen, Cameron; Hendricks, Sharief; Fitzpatrick, Anna; Naylor, Adam; Robertson, Colin; Jones, Ben
ABSTRACT: Rugby league has a relatively high injury risk, with the tackle having the greatest injury propensity. The number of tackles players engage in, prior to injurious tackles may influence injury risk, which has yet to be investigated. Therefore, this study investigated if rugby league players are involved in more tackles (as either tackler or ball carrier) (i) in the 10 minutes, or (ii) 1-min periods prior to an injurious tackle-event, (iii) differences for ball carriers vs . tacklers, and (iv) forwards vs . backs. Video analysis was utilised to quantify the number and rate of tackles in the 10-min periods prior to 61 tackle-related injuries. One thousand two hundred and eighty 10-min periods where players were not injured, were used as matched-controls. Generalized mixed linear models were used to analyse mean total and rate for tackles. Injured players were involved in significantly fewer tackles during the 10-min period, yet significantly more tackles during the final minute prior to the injurious tackle-event, compared to non-injured players. There were no differences between ball carriers vs . tacklers during the 10-min period. Both injured position groups were involved in significantly more tackles in the final minute. Additional match data sources are needed to further inform injury preventive strategies of tackle events.